Development and Internal Validation of a Clinical Prediction Model for 90-Day Walking Recovery Following Hip Hemiarthroplasty in Elderly Patients with Neck of Femur Fracture in Nigeria - Kehinde Adesola Alatishe; Wakeel Olaide Lawal; Taiwo Adedamola Alatishe; Opeyemi Qozeem Asafa; Michael Ebiyon Ugbeye; Olatunji Sulaimon Olanrewaju (Archives of Orthopaedics, 2026)
Background: Early mobilization following hip hemiarthroplasty for neck of femur (NOF) fractures is critical to reducing morbidity and mortality in elderly patients. Objective tools to predict short-term walking recovery are lacking. Objectives: To develop and internally validate a clinical prediction model for 90-day postoperative walking recovery in elderly patients following hip hemiarthroplasty for neck of femur fracture in Nigeria. Methods: This retrospective cohort study evaluated elderly patients with NOF fractures treated via hemiarthroplasty (January 2018–December 2022). Patients with unstable intertrochanteric or pathologic fractures, incomplete records, or 90-day mortality were excluded. Predictor variables were screened using univariable logistic regression. Factors with p